Czech Republic : Selected Issues. (IMF Staff Country Reports; Country Report, 2013)
This Selected Issues paper analyzes the fiscal strength of the economy of the Czech Republic. Fiscal policy in the Czech Republic has shown a procyclical bias temporarily interrupted during the crisis years. The large stimulus implemented has been more than compensated by a frontloaded adjustment. However, the fiscal framework could be improved to increase transparency, predictability, and credibility of policy and minimize the procyclical bias. This could be achieved by incorporating, among other things, a simple and credible rule with a medium-term fiscal anchor set in structural terms.